Financing of SMEs and Credit Risk: The Inevitable 5Cs - Bhatt, Nidhi (Journal of Commerce and Trade, 2012)
Financing of Small and Medium Enterprises, popularly known as SMEs, is a priority for banks. These little growth engines play a crucial role in the overall economic development of the country as they contribute greatly in terms of output, exports and employment. But as the sector is characterized by information asymmetries, high processing cost and unsophisticated management; financing of SMEs remains a major policy concern. Whenever we talk of strategic areas for SME Banking performance, Credit Risk Management emerges out to be an important one. Assessing credit risk involved in the proposal of small entrepreneurs is a challenging task which is culminated by means of a proper study of the famous five Cs– Character, Capacity, Capital, condition and Collateral. The paper analyzes these inevitable factors in relation to the financing of SMEs.